Effects of total fat intake on bodyweight in children - Naude, Celeste E (Cochrane Database Syst Rev, 2018)
BACKGROUND: As part of efforts to prevent childhood overweight and obesity, we need to understand the relationship between total fat intake and body fatness in generally healthy children. OBJECTIVES: To assess the effects of total fat intake on measures of weight and body fatness in children and young people not aiming to lose weight. SEARCH METHODS: For this update we revised the previous search strategy and ran it over all years in the Cochrane Library, MEDLINE (Ovid), MEDLINE (PubMed), and Embase (Ovid) (current to 23 May 2017). No language and publication status limits were applied. We searched the World Health Organization International Clinical Trials Registry Platform and ClinicalTrials.gov for ongoing and unpublished studies (5 June 2017). SELECTION CRITERIA: We included randomised controlled trials (RCTs) in children aged 24 months to 18 years, with or without risk factors for cardiovascular disease, randomised to a lower fat (30% or less of total energy (TE)) versus usual or moderate‐fat diet (greater than 30%TE), without the intention to reduce weight, and assessed a measure of weight or body fatness after at least six months. We included prospective analytical cohort studies in these children if they related baseline total fat intake to weight or body fatness at least 12 months later. We duplicated inclusion decisions and resolved disagreement by discussion with other authors. DATA COLLECTION AND ANALYSIS: We extracted data on participants, interventions or exposures, controls and outcomes, and trial or cohort quality characteristics, as well as data on potential effect modifiers, and assessed risk of bias for all included studies. We extracted outcome data using the following time point ranges, when available: RCTs: baseline to six months, six to 12 months, one to two years, two to five years and more than five years; cohort studies: baseline to one year, one to two years, two to five years, five to 10 years and more than 10 years. We planned to perform random‐effects meta‐analyses with relevant subgrouping, and sensitivity and funnel plot analyses where data allowed. MAIN RESULTS: We included 24 studies comprising three parallel‐group RCTs (n = 1054 randomised) and 21 prospective analytical cohort studies (about 25,059 children completed). Twenty‐three were conducted in high‐income countries. No meta‐analyses were possible, since only one RCT reported the same outcome at each time point range for all outcomes, and cohort studies were too heterogeneous. For the RCTs, concerns about imprecision and poor reporting limited our confidence in our findings. In addition, the inclusion of hypercholesteraemic children in two trials raised concerns about applicability. Lower versus usual or modified total fat intake may have made little or no difference to weight over a six‐ to twelve month period (mean difference (MD) ‐0.50 kg, 95% confidence interval (CI) ‐1.78 to 0.78; 1 RCT; n = 620; low‐quality evidence), nor a two‐ to five‐year period (MD ‐0.60 kg, 95% CI ‐2.39 to 1.19; 1 RCT; n = 612; low‐quality evidence). Compared to controls, lower total fat intake (30% or less TE) probably decreased BMI in children over a one‐ to two‐year period (MD ‐1.5 kg/m(2), 95% CI ‐2.45 to ‐0.55; 1 RCT; n = 191; moderate‐quality evidence), with no other differences evident across the other time points (two to five years: MD 0.00 kg/m(2), 95% CI ‐0.63 to 0.63; 1 RCT; n = 541; greater than five years; MD ‐0.10 kg/m(2), 95% CI ‐0.75 to 0.55; 1 RCT; n = 576; low‐quality evidence). Lower fat intake probably slightly reduced total cholesterol over six to 12 months compared to controls (MD ‐0.15 mmol/L, 95% CI ‐0.24 to ‐0.06; 1 RCT; n = 618; moderate‐quality evidence), but may make little or no difference over longer time periods. Lower fat intake probably slightly decreased low‐density lipoprotein (LDL) cholesterol over six to 12 months (MD ‐0.12 mmol/L, 95% CI ‐0.20 to ‐0.04; 1 RCT; n = 618, moderate‐quality evidence) and over two to five years (MD ‐0.09, 95% CI ‐0.17 to ‐0.01; 1 RCT; n = 623; moderate‐quality evidence), compared to controls. However, lower total fat intake probably made little or no difference to HDL‐C over a six‐ to 12‐month period (MD ‐0.03 mmol/L, 95% CI ‐0.08 to 0.02; 1 RCT; n = 618; moderate‐quality evidence), nor a two‐ to five‐year period (MD ‐0.01 mmol/L, 95% CI ‐0.06 to 0.04; 1 RCT; n = 522; moderate‐quality evidence). Likewise, lower total fat intake probably made little or no difference to triglycerides in children over a six‐ to 12‐month period (MD ‐0.01 mmol/L, 95% CI ‐0.08 to 0.06; 1 RCT; n = 618; moderate‐quality evidence). Lower versus usual or modified fat intake may make little or no difference to height over more than five years (MD ‐0.60 cm, 95% CI ‐2.06 to 0.86; 1 RCT; n = 577; low‐quality evidence). Over half the cohort analyses that reported on primary outcomes suggested that as total fat intake increases, body fatness measures may move in the same direction. However, heterogeneous methods and reporting across cohort studies, and predominantly very low‐quality evidence, made it difficult to draw firm conclusions and true relationships may be substantially different. AUTHORS' CONCLUSIONS: We were unable to reach firm conclusions. Limited evidence from three trials that randomised children to a lower total fat intake (30% or less TE) versus usual or modified fat intake, but with no intention to reduce weight, showed small reductions in body mass index, total‐ and LDL‐cholesterol at some time points with lower fat intake compared to controls, and no consistent differences in effects on weight, high‐density lipoprotein (HDL) cholesterol or height. Associations in cohort studies that related total fat intake to later measures of body fatness in children were inconsistent and the quality of this evidence was mostly very low. Twenty‐three out of 24 included studies were conducted in high‐income countries, and may not be applicable in low‐ and middle‐income settings. High‐quality, longer‐term studies are needed, that include low‐ and middle‐income settings and look at both possible benefits and risks.